An Efficient Ultra‐Flexible Photo‐Charging System Integrating Organic Photovoltaics and Supercapacitors. Issue 20 (6th April 2020) - Liu, Ruiyuan; Takakuwa, Masahito; Li, Ailong; Inoue, Daishi; Hashizume, Daisuke; Yu, Kilho; Umezu, Shinjiro; Fukuda, Kenjiro; Someya, Takao
Abstract: Flexible and biocompatible integrated photo‐charging devices consisting of photovoltaic cells and energy storage units can provide an independent power supply for next‐generation wearable electronics or biomedical devices. However, current flexible integrated devices exhibit low total energy conversion and storage efficiency and large device thickness, hindering their applicability towards efficient and stable self‐powered systems. Here, a highly efficient and ultra‐thin photo‐charging device with a total efficiency approaching 6% and a thickness below 50 µm is reported, prepared by integrating 3‐µm‐thick organic photovoltaics on 40 µm‐thick carbon nanotube/polymer‐based supercapacitors. This flexible photo‐charging capacitor delivers much higher performance compared with previous reports by tuning the electrochemical properties of the composite electrodes, which reduce the device thickness to 1/8 while improving the total efficiency by 15%. The devices also exhibit a superior operational stability (over 96% efficiency retention after 100 charge/discharge cycles for one week) and mechanical robustness (94.66% efficiency retention after 5000 times bending at a radius of around 2 mm), providing a high‐power and long‐term operational energy source for flexible and wearable electronics. Abstract : Integrating flexible organic photovoltaics with a carbon nanotube/polymer‐based supercapacitor on a 1‐µm‐thick ultrathin substrate for the first time enables an efficient and ultra‐flexible design. It exhibits a total system efficiency approaching 6% and a thickness below 50 µm, and a superior 94.66% efficiency retention after 5000 bending cycles at a radius of around 2 mm.